Design and fabricate of portable "Tabung Masjid" - Mohamad Noor Elya, Yahaya (2009)
This report presents about the design and fabrication of portable “Tabung Masjid” that always been used especially in mosque. This portable “Tabung Masjid” is a device which is important in order to make people comfortable in donation. The idea of the fabricating of this “Tabung Masjid” is based on student’s creativity. The selection of suitable materials in fabricating of this “Tabung Masjid” is has minimum weight, long life-span and can detain heavy load. Material proposed for the fabrication of the “Tabung Masjid” is stainless steel material. In this report, we’ll also be having more to the fabrication of this portable “Tabung Masjid”.